UPAYA MELATIH KEMANDIRIAN BELAJAR MELALUI OUTDOOR LEARNING (ODL) SISWA KELAS III SDN PUCANG 4 SIDOARJO - Rosyi Umami (PRODI PGSD STKIP PGRI SIDOARJO, 2020)
In doing interaction during learning process in the classroom, most of the students are less independence. This research is an effort to practice independent of students’ learning through outdoor learning. The approach used in this research is qualitative. However, this research method used is descriptive. This research use qualitative approach which is a research that produce descriptive data such as writing and speaking words from people and the activities that can be observed. Based on the result of students’ learning observation, the mean value of students’ activities in first meeting is 2,967, the second meeting is 3,562, and the last meeting is 3,931. The conclusion of this research show that the third grade students of SD Negeri Pucang 4 Sidoarjo are very enthusiastic and happy in learning process. Therefore, the interaction of learning process can be done based on our hope.